2017
DOI: 10.1037/aca0000127
|View full text |Cite
|
Sign up to set email alerts
|

From moment-to-moment to day-to-day: Experience sampling and diary investigations in adults’ everyday creativity.

Abstract: Two studies examined the dynamics and predictors of momentary creative activity among adults. Study 1 (N = 74) applied the experience sampling methodology (ESM) to investigate the likelihood of engaging in creative activity and explain its variability using both within-person predictors (experienced emotions) and between person-predictors (personality and creative activity). This study also demonstrated that the likelihood of momentary creative activity during a random week at the age 52 is predicted by partic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
57
0
1

Year Published

2018
2018
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 74 publications
(62 citation statements)
references
References 63 publications
4
57
0
1
Order By: Relevance
“…Cooking is a form of personal and social creativity that is grounded in the familiar, and infused with cultural values of self-expression and pleasing the family. Karwowski, Lebuda, Szumski and Firkowska-Mankiewicz (2017) presented two studies that examined the dynamics and predictors of momentary creative activity among adults. The results indicated that active positive emotions predicted day-to-day variability of creative behaviour, whereas the role of individual-differences was more complex and domain-specific.…”
Section: Everyday Creativity: Backgrounds and Methodological Aspectsmentioning
confidence: 99%
See 1 more Smart Citation
“…Cooking is a form of personal and social creativity that is grounded in the familiar, and infused with cultural values of self-expression and pleasing the family. Karwowski, Lebuda, Szumski and Firkowska-Mankiewicz (2017) presented two studies that examined the dynamics and predictors of momentary creative activity among adults. The results indicated that active positive emotions predicted day-to-day variability of creative behaviour, whereas the role of individual-differences was more complex and domain-specific.…”
Section: Everyday Creativity: Backgrounds and Methodological Aspectsmentioning
confidence: 99%
“…Participants' expressions are related to previous studies that indicate the impact of creative activities on the general well-being of people (Richard, 2010) and the development of positive emotions (Benedek, Jauk, Kerschenbauer, Anderwald, & Grond, 2017;Silvia, 2015;Conner, DeYoung, & Silvia, 2018;Karwowski, Lebuda, Szumski, & Firkowska-Mankiewicz, 2017;Silvia, al, 2014). Participants use words such as happiness, pleasure, relief, relaxation and satisfaction to define how they feel during and after creative activities.…”
Section: Emotions In Playmentioning
confidence: 96%
“…Las expresiones de los participantes se relacionan con estudios anteriores que indican los impactos de las actividades creativas en el bienestar general de las personas (Richard, 2010) y el desarrollo de emociones positivas (Benedek, Jauk, Kerschenbauer, Anderwald y Grond, 2017;Conner, DeYoung y Silvia, 2018;Karwowski, Lebuda, Szumski y Firkowska-Mankiewicz, 2017;Silvia et al, 2014). Los participantes usan palabras como felicidad, placer, alivio, relajación y satisfacción para definir cómo se sienten durante y después de las actividades creativas.…”
Section: Emociones En El Proceso Creativounclassified
“…Theories -Research -Applications 5(2) 2018 portant for understanding creative learning, but generalize to creativity science as a whole. In recent years, creativity researchers have recognized this and started using a variety of more sensitive and dynamic techniques, including: ecological momentary assessment (Czerwonka, 2019;Karwowski, Lebuda, Szumski, & Firkowska -Mankiewicz, 2017;Silvia et al, 2014), passive automatized measurement (D'Mello, Dieterle, & Duckworth, 2017), rigorous observational studies Katz-Buonincontro & Anderson, 2018), and blended approaches that link solid cognitive measures with a look into individuals' strategies, while dealing with creative tasks (Jankowska, Czerwonka, Lebuda, & Karwowski, 2018;Loesche, Goslin, & Bugmann, 2018).…”
Section: Considerations For Promoting Favorable Consequences Of Creatmentioning
confidence: 99%